2010
DOI: 10.1111/j.1365-2249.2010.04149.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of human placenta cytotrophoblast cells on the maturation and T cell stimulating ability of dendritic cellsin vitro

Abstract: SummaryThe success of pregnancy depends upon regulatory mechanisms that allow the fetus to survive and develop to term in the uterus, despite maternal immune cells' awareness of paternal alloantigens. At least some of these specific mechanisms are mediated by the effect of fetal trophoblast cells. In the present study we examine the effect of human placental cytotrophoblast cells (CTCs) on the maturation of dendritic cells (DCs) in vitro. For that purpose, CTCs were isolated from samples of placentae at 5-11 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…CD14 is often considered a marker of macrophages, with which dendritic cells are closely related. It has, however, been shown that CD14 expression is retained in dendritic cells when they develop in the presence of trophoblasts (Talayev et al 2010). These facts, together with the source of cells in this experiment, suggest that these are uterine dendritic cells and thus of maternal origin (Kammerer et al 2000;Tagliani and Erlebacher 2011).…”
Section: Maternal Cells Uterine Dendritic Cells (Dcs; Cluster 4)mentioning
confidence: 59%
See 1 more Smart Citation
“…CD14 is often considered a marker of macrophages, with which dendritic cells are closely related. It has, however, been shown that CD14 expression is retained in dendritic cells when they develop in the presence of trophoblasts (Talayev et al 2010). These facts, together with the source of cells in this experiment, suggest that these are uterine dendritic cells and thus of maternal origin (Kammerer et al 2000;Tagliani and Erlebacher 2011).…”
Section: Maternal Cells Uterine Dendritic Cells (Dcs; Cluster 4)mentioning
confidence: 59%
“…These cells lack expression of CD19, CD209, and CD163 but express the combination of markers ITGAX + / CD14 + /CD4 + /CD83 + / CD86 + . The genes CLEC4C, THBD, CD1C, CD80, IL10, and IL12B that characterize some of the decidual DCs (Kammerer et al 2008;Talayev et al 2010) were not found. CD14 is often considered a marker of macrophages, with which dendritic cells are closely related.…”
Section: Maternal Cells Uterine Dendritic Cells (Dcs; Cluster 4)mentioning
confidence: 99%
“…Several human and murine studies proposed trophoblast-associated factors as potential candidates in DC modulation (9, 10). This includes factors, such as soluble thymic stromal lymphopoitin and pregnancy-specific glycoprotein (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…A suspension of peripheral blood mononuclear cells (PBMCs) was isolated by the centrifugation in a ficoll-verografin density gradient (1.077 g/cm 3 ). DCs were generated by the standard method [5]. PBMCs (1-5 × 10 6 cells/mL) were resuspended in a complete nutrition media (CNM; RPMI 1640 supplemented with 10% fetal calf serum, 1 mM HEPES, 2 mM L glutamin, and 100 μg/mL streptomycin), then plated on 24 well polystyrene plates (Costar, United States), 2 mL per well, and cultured for 3 h at 37°C and 5% CO 2 .…”
Section: Leptin and Ghrelin Regulate Dendritic Cell Maturation And Dementioning
confidence: 99%
“…Physiologic saline used for dissolving the hormones was added to the control samples. Granulocyte-macrophage colony stimulating factor (GM CSF) (100 ng/mL, R&D, United States) and IL 4 (20 ng/mL, BioLegend, United States) were added for the induction of DC formation in the sam ples [5]. The cells were incubated at 37°C and 5% CO 2 for 5 days.…”
Section: Leptin and Ghrelin Regulate Dendritic Cell Maturation And Dementioning
confidence: 99%